Some Vector FK Sequence Spaces Generated by Modulus Function - Herawati, E.; N. Irsyad; E. Rosmaini (Talenta Publisher, 2020)
In this paper, some vector valued sequence spaces and using modulus function are presented. Furthermore, we examined some topological properties of these sequence spaces equipped with a paranorm.